Implementation of Closed Loop on SME (Case Study of Natural Color Batik Siputri Semarang) - Kurniawan, Gabriella Angel; Untari, Rustina (Journal of Management and Business Environment (JMBE), 2025)
This research aims to find out how can the closed loop is implemented at the Natural Color Batik Siputri and what are the benefits possibly obtained. The research is a qualitative. Interviews were conducted with the owner of Siputri Natural Color Batik and was followed with a direct observation at the production site. The research focused on the coloring process. The batik dyeing process produces liquid and wastes which are processed for watering plants. The research results show that SMEs can implement the closed-loop concept. In Natural Color Batik SME, the closed loop can provide benefits for SMEs by guaranteeing the availability of dye raw materials in the expected quality and quantity. Implementing a closed loop can minimize production costs.The implementation of closed-loop on Siputri Natural Color Batik cannot yet be done comprehensively. Three of the five plants used for dying the batik were not cultivated by the firm. This is due to difficulties in finding seeds and the size of the plants which are quite large. Siputri Natural Color Batik is an example of an SME that can implement a closed loop.